Aging in Place: Social Connectedness and the Health of Older Subsidized Housing Residents. (17th December 2021) - Cudjoe, Thomas; Gonyea, Judith; Stone, Robyn
Abstract: Findings on the prevalence and impacts of loneliness and social isolation on the lives of older adults have led to the lack of social connectedness being viewed as a major public health issue. Although an understudied population, emerging evidence suggests that for the nearly 3 million older low-income adults living in subsidized housing the impacts of lack of social connection may be especially profound. From a life course perspective, "cumulative economic disadvantage, " if combined with a "cumulative connectedness disadvantage, " may heighten exposure to health risk factors and negative health outcomes. Addressing social risk factors in this population thus may have the potential to reduce health disparities as well as improve quality of life. Decades of epidemiologic evidence suggest that social isolation is a key factor in disparate outcomes. Evidence-based interventions are needed to improve aging in place for this population, but little is known about the individual or contextual factors that influence social connectedness and health among this high-risk population of older adults. This symposium includes interdisciplinary perspectives and methods as well as present results from four studies that examine 1) perspectives on aging in place in subsidized housing, 2) relationship between social connection and food insecurity 3) relationship between social isolation and healthcare utilization and 4) between resident ties and links to health outcomes. Papers in this symposium will highlight the implications of study findings for informing future interventions to improve aging in place for older adults living in subsidized housing.